PENGARUH RELIGIUSITAS TERHADAP JUVENILE DELINQUENCY PADA SISWA SMA NEGERI 2 MANADO - Yehezkiel J. Pua; Tellma M. Tiwa; Great E. Kaumbur (PSIKOPEDIA, 2022)
One of the problems one faces in adolescence is a transition period that can make a youth's emotions less stable. This time is often referred to as the time of the storm (strum and drang), yaigrumbling about a time of turmoil resulting from opposing values. It is this transition period that brings about a sense of self-behavior called Juvenile Delinquency. Juvenile Delinquency is a manifestation of unresolved conflicts in both childhood and youth. This requires strong religious confidence and experience in the teachings of religion in order to reduce delinquent behavior. The study was carried out using the quantitative method to see the religious impact of the juvenile delinquency of country high school students 2 Manado. The sample in this study totaled 74 students. The data analysis technique used in data management is simple linear regression. Management used computer assistive SPSS program 26 for Windows. The calculations using a simple regression analysis gained significance by 0.002 (p< 0.05) then would have a religious influence on juvenile delinquency with a contribution of 12.9%. Autism